2020
DOI: 10.1016/j.ssci.2020.104862
|View full text |Cite
|
Sign up to set email alerts
|

A multicriteria approach for risk assessment of Covid-19 in urban district lockdown

Abstract: At the beginning of 2020, the spread of a new strand of Coronavirus named SARS-CoV-2 (COVID-19) raised the interest of the scientific community about the risk assessment related to the viral infection. The contagion became pandemic in few months forcing many Countries to declare lockdown status. In this context of quarantine, all commercial and productive activities are suspended, and many Countries are experiencing a serious crisis. To this aim, the understanding of risk of contagion in every urban district i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 28 publications
1
43
0
2
Order By: Relevance
“…Risk assessment: In [516] , an ANN is used to perform risk assessment of covid-19 in urban districts. The importance of employing AI-based search tools is discussed in [517] and it is argued that future research into the disease requires smart searching techniques.…”
Section: Applications Of Ai In Epidemiologymentioning
confidence: 99%
“…Risk assessment: In [516] , an ANN is used to perform risk assessment of covid-19 in urban districts. The importance of employing AI-based search tools is discussed in [517] and it is argued that future research into the disease requires smart searching techniques.…”
Section: Applications Of Ai In Epidemiologymentioning
confidence: 99%
“…To support administrative decisions regarding the best strategies to restrict or restart local activities, disease risk indices predict the risk of disease transmission in geographic regions. 47 , 48 Epidemiological data can inform risk of contracting the virus through community spread. 49 Risk-based surveillance enhances the ability to detect expected new cases as soon as possible by identifying those who are more likely to be infected than others.…”
Section: Data Integration and Surveillancementioning
confidence: 99%
“… 50 Insights into risk forecasting can be extracted from previous outbreaks 51 , 52 and early views of the current pandemic. 47 , 48 …”
Section: Data Integration and Surveillancementioning
confidence: 99%
“…Several previous studies have revealed the parameters associated with this risk of COVID. In those papers [17], parameters involved in the risk of COVID transmission were described and classified into criteria, sub-criteria and intensity as shown in Figure 1. In addition, Acharya [18] in his paper also proposed the vulnerability index that affects COVID.…”
Section: Covid-19 Risk Parametersmentioning
confidence: 99%